Fuzzifying the Socio-Economic Status of a Person: Using Fuzzy Logic to Assess Socio-Economic Status (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper makes an attempt to inquire, evaluate and interpret the “socio-economic world” of a person using fuzzy logic. In the context of socio-economic, a degree of poverty is analyzed to show a status of a person. Fuzzy membership functions are applied to the attributes relating to poverty measurement with reference to issues like income, consumption, education and employment, environment, gender disparity, equality, preferential options and even health conditions. Fuzzy multi-dimensional approach is proposed to determine to what extent someone is poor.